Spectrum and Network Measurements - Witte, Robert A. (SciTech Publishing Inc, 2001)
This book is about the theory and practice of spectrum and network measurements in electronic systems. It is intended for readers who have a background in electrical engineering and use spectrum analyzers and network analyzers to characterize electronic signals or systems in the frequency domain. The book can certainly be read cover to cover, but it is also organized into independent chapters and subchapters. This allows the reader to read selectively and enhances the usefulness of the book as a reference. Chapter 1 is an introduction to spectrum and network measurements. Decibels are an often used and misused concept so Chapter 2 is devoted to that topic. Fourier theory, the theoretical basis for spectrum analysis, is summarized in Chapter 3. The two main types of spectrum analyzers (FFT analyzers and swept analyzers) are discussed in Chapters 4 and 5. Chapters 6 through 9 cover several important measurement applications: modulated signals, signal distortion, noise, and pulsed waveforms. Averaging and filtering are covered together in Chapter 10. Chapters 11 and 12 cover transmission lines and measurement connection techniques. Chapter 13 introduces two-port network theory, which is the basis for network analysis. Chapters 14 through 16 cover network analyzers and their use in making transmission and reflection measurements. Chapter 17 ends the book with a discussion of instrument performance and specifications
orig. ed. 1993 by Prentice Hall
Keywords: Frequenzanalyse; Messung; Nachrichtentechnik; Frequenzbereich; Elektrische Messtechnik; Netzwerkanalyse; Electric distortion; Fourier transformations; Modulation (Electronics); Modulation theory; Spectral analysis; Spectrum analyzers